2020
DOI: 10.1002/adfm.201908633
|View full text |Cite
|
Sign up to set email alerts
|

Galvanically Replaced, Single‐Bodied Lithium‐Ion Battery Fabric Electrodes

Abstract: Despite extensive research on flexible/wearable power sources, their structural stability and electrochemical reliability upon mechanical deformation and charge/discharge cycling have not yet been completely achieved. A new class of galvanically replaced single-bodied lithium-ion battery (LIB) fabric electrodes is demonstrated. As a proof of concept, metallic tin (Sn) is chosen as an electrode active material. Mechanically compliable polyethyleneterephthalate (PET) fabrics are conformally coated with thin meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In recent researches, the most commonly used flexibility evaluation method is to perform the electrochemical measurement after bending the supercapacitors to a certain degree or multiple times, which actually evaluates the static flexibility of supercapacitors. Although a few works conducted flexibility measurements under dynamic bending, the bending strain rates were relatively low (60 s per bending cycle or strain rate of 2.1% s –1 ) and obviously different from normal human movements. Moreover, these researches used relatively high scan rates (100–200 mV s –1 ), which will lead to the reduction in the time scale of electrochemical step and increase in current signal .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In recent researches, the most commonly used flexibility evaluation method is to perform the electrochemical measurement after bending the supercapacitors to a certain degree or multiple times, which actually evaluates the static flexibility of supercapacitors. Although a few works conducted flexibility measurements under dynamic bending, the bending strain rates were relatively low (60 s per bending cycle or strain rate of 2.1% s –1 ) and obviously different from normal human movements. Moreover, these researches used relatively high scan rates (100–200 mV s –1 ), which will lead to the reduction in the time scale of electrochemical step and increase in current signal .…”
Section: Results and Discussionmentioning
confidence: 99%
“…To quantitatively separate the proportion of the pseudocapacitance effect and the diffusion Faraday embedding in the energy storage process, the pseudocapacitance contribution is calculated by Eqs. (7)(8) [27]: where k 1 and k 2 are related constants. The first term on the right of Eq.…”
Section: Potassium Storage Performancementioning
confidence: 99%
“…Potassium-ion batteries (PIBs) are considered as potential substitutes because of their high abundance, lower cost, closer to the standard potential of LIBs, and safer potassium potential (0.2 V) [2,3]. To improve the flexibility and safety of ESDs for wearable electronics, a lot of research has been done on device structure design [4][5][6]: Woo et al [7] used the electric displacement reaction to prepare the fabric electrode for integrated LIBs. Zhu et al [8] used photographic printing technology to grow active materials on rice paper substrate as flexible electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al developed a Cu-coated 3D soft fabric anode that showed superior cell performance under optimized mechanical stress, using a two-step dip-coating method in which copper is applied to various dielectric fabrics to make them electrically conductive and suitable for lithium metal anode applications. 3 Woo et al 4 proposed electroplated substituted monomeric Sn@Ni fabric electrodes as a novel approach to develop high-performance LIB electrodes with excellent reduction-reaction rates and general formability. The nickel nanolayer was replaced by tin plating on the PET fabric, which was integrally embedded in the nickel matrix, driven by the electrochemical difference in potential between nickel and tin.…”
Section: Introductionmentioning
confidence: 99%
“…The peculiar fabric electrode structure for monomeric Sn@ Ni may originate from the interconnected ion transport channels and electron conduction networks. 4 However, compared with fabric batteries, yarn batteries have the advantages of being lightweight, small in size, and various structures, which have attracted the attention of many scholars. 5 Being easily incorporated into commercially available textiles, they are better suited for intelligent printable textile use than membrane devices.…”
Section: Introductionmentioning
confidence: 99%